2020
DOI: 10.1177/1074248420922793
|View full text |Cite
|
Sign up to set email alerts
|

A MicroRNA Signature in Acute Coronary Syndrome Patients and Modulation by Colchicine

Abstract: Background: Circulating microRNAs (miRNAs) may play a pathogenic role in acute coronary syndromes (ACS). It is not yet known if miRNAs dysregulated in ACS are modulated by colchicine. We profiled miRNAs in plasma samples simultaneously collected from the aorta, coronary sinus, and right atrium in patients with ACS. Methods: A total of 396 of 754 miRNAs were detected by TaqMan real-time polymerase chain reaction from EDTA-plasma in a discovery cohort of 15 patients (n = 3 controls, n = 6 ACS standard therapy, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…We profiled 754 known/ validated human miRNAs using OpenArray panels on the discovery set of samples. As expected for plasma samples [38,39], 273 miRNAs were expressed in at least one of the samples (Fig. 1a); with the remaining miRNAs being undetectable (C t value = 39).…”
Section: Resultssupporting
confidence: 78%
“…We profiled 754 known/ validated human miRNAs using OpenArray panels on the discovery set of samples. As expected for plasma samples [38,39], 273 miRNAs were expressed in at least one of the samples (Fig. 1a); with the remaining miRNAs being undetectable (C t value = 39).…”
Section: Resultssupporting
confidence: 78%
“…Clinically high levels of Nourin were detected in ACS and AMI patients, but not in symptomatic noncardiac patients and healthy subjects [17], suggesting a potential use of the Nourin biomarker to rule out myocardial ischemia for symptomatic patients having noncardiac causes. Recently, aberrant miRNAs have been reported to play a role in the pathogenesis of cardiovascular diseases, and they are involved in vascular dysfunction, apoptosis, autophagy, inflammation, and angiogenesis [9,18,[31][32][33]. In the present study, we applied a bioinformatics analysis to elucidate the underlying molecular mechanism associated with Nourin protein, and accordingly, the topological characteristics between Nourin protein sequence and miRNAs-mediated interactions network associated with myocardial ischemia were retrieved.…”
Section: Discussionmentioning
confidence: 99%
“…40 In addition, the follow-up was also short, as 3 studies 40,43,44 reported only 1-month follow-up duration and 1 study 41 reported a 12-month follow-up period. The duration of colchicine treatment is also heterogeneous, varying between 1 day, 36,38,40,42 5 days, 35 1 month, 43,44 and 1 year. 41 The contradictory results regarding the effect of colchicine on hs-CRP levels could be explained by differences in baseline values between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Colchicine significantly lowered the expression of 12 miRNAs, demonstrating once again its potential role in reducing acute inflammation. 42…”
Section: Colchicine and Acute Myocardial Infarctionmentioning
confidence: 99%
See 1 more Smart Citation